5x-4-7x=3x+6

Simple and best practice solution for 5x-4-7x=3x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-4-7x=3x+6 equation:


Simplifying
5x + -4 + -7x = 3x + 6

Reorder the terms:
-4 + 5x + -7x = 3x + 6

Combine like terms: 5x + -7x = -2x
-4 + -2x = 3x + 6

Reorder the terms:
-4 + -2x = 6 + 3x

Solving
-4 + -2x = 6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-4 + -2x + -3x = 6 + 3x + -3x

Combine like terms: -2x + -3x = -5x
-4 + -5x = 6 + 3x + -3x

Combine like terms: 3x + -3x = 0
-4 + -5x = 6 + 0
-4 + -5x = 6

Add '4' to each side of the equation.
-4 + 4 + -5x = 6 + 4

Combine like terms: -4 + 4 = 0
0 + -5x = 6 + 4
-5x = 6 + 4

Combine like terms: 6 + 4 = 10
-5x = 10

Divide each side by '-5'.
x = -2

Simplifying
x = -2

See similar equations:

| 200=3x+7 | | 9(8d*5)+13=12d-2 | | -15=-6+x | | 4r-10=2r+16 | | 5(4-2y)=8(3y-2) | | -3(6a-3)+8a=-1 | | 3.1t+7=2.6 | | 3x-6=8x-26 | | 0.8(y-5)=10 | | 5(3k-2)=4(3-5k) | | -9(2-y)-(2-y)=2 | | -x-4=3x-4 | | 6(2g-4)-(3g-7)=1 | | xy^4+x^2y=5x+3y | | 14.6=k/2.5 | | 3n+53=99 | | 3x-1=6x+8 | | 3x-6+2x+3+8x-26=180 | | 3(2x-1)-3=4(-3x+2) | | 9(3-2n)+11n=2 | | 8g+5=-3(g+2) | | y/10+5=-14 | | 2(4x-3)=(6x+4) | | x^2+1800=90x | | 2(3c-6)=5c+8 | | -6-7x+3x=38 | | 5=z+13 | | 8x-3(x-5)=2(x-4)+1 | | -4(3a+5)=-7(2a-5) | | 5(y-3)=3(2y-4) | | x/6+3=6-x/6 | | 3.4y=8.5 |

Equations solver categories